The Role Of Local Culture in Forming The Indentity of Spacial A study of Balinese culture in spatial planning in the city of Denpasar - Gusti Putu Anindya Putra (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Denpasar as the Capital of the Province of Bali should reflect a strong Balinese cultural identity, but in reality this cultural identity has changed along with the course of history and its development process. This study examines the role of Balinese culture in shaping spatial identity, by focusing on how the development of catus patha as a reference for the formation of spatial structures and patterns based on Balinese culture in modern society. Designed with qualitative research, this study collects data through observation, interviews, and documentation studies. The collected data were analyzed using semiotic theory and structural functional theory supported by ethnographic theory which was applied in an eclitic manner. The results of this study indicate that there is a change in the function and arrangement of the catus patha in spatial planning caused by multicultural community factors, the function of space that is not accommodated in the Balinese cultural concept, the existence of two forms of traditional village and village/kelurahan government, as well as changes in the use of the basic dimensions of the sikut /gegulak becomes a metric. The form of change occurs at the level of form, concept and philosophy with changes in function, form, material and technology; fusion of Balinese cultural symbols in a modern layout. The implication is that there is a diversity of shapes, materials, colors that do not refer to Balinese culture; changes in hierarchy and function, structure and spatial patterns based on Balinese culture; land compression and land conversion; the blurring of urban identity, overlapping areas and boundaries of traditional villages with villages/kels, and people disobeying the use of Balinese cultural attributes and symbols. This study proposes a strategy by rebuilding the values of Balinese cultural identity, through literacy, classification and zoning of new functions, synchronizing the authority of traditional villages and villages/kelurahan, and converting basic dimensions into development guidelines. The implication is that there is a diversity of forms in the frame of Balinese Cultural Identity, sublimation occurs, universally understood; society can adapt to adaptation to technology, so that regulatory forces play a role in compliance with its application; reinforcing city characteristics; symbols as Balinese cultural identity become part of the development process; and its application as discretion in the form of regulation. This study offers two findings, namely (1) related to the fact that Balinese culture in spatial planning has been applied in the preparation of the Denpasar city spatial plan but has not been implemented properly; (2) which shows that Balinese cultural identity in spatial planning is universal, has the ability to absorb external cultural elements while being able to maintain the uniqueness of its cultural identity.